2021
DOI: 10.1002/pbc.29302
|View full text |Cite
|
Sign up to set email alerts
|

Parental adjustment following their child's completion of acute lymphoblastic leukemia treatment

Abstract: Background Few studies haveexamined parent and family adaptation in the early period following the end of childhood cancer treatment. We examined parent adjustment at the end of their child's treatment for acute lymphoblastic leukemia (ALL). Methods Parents of childhood cancer survivors (CCS), who were 3 months post‐ALL treatment, and parents of typically developing children completed measures of psychological and family functioning. Parents of CCS also completed distress and posttraumatic stress symptom (PTSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
1
8
0
3
Order By: Relevance
“…Second, the lack of a positive finding may have been due to Cascade’s preventative approach, which did not restrict enrolment to parents with poor HRQL or high distress. Aligning with parents in other studies [ 23 , 72 , 73 , 74 ], many of our participating parents actually reported good HRQL and low depression/anxiety at baseline (Q1) and may have had a low need for further help, limiting the relative improvement that could be achieved. It is possible that a program delivered further off treatment, when survivors’ risk of late medical complications and challenges of developing independence into adulthood are increased, may be more effective.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Second, the lack of a positive finding may have been due to Cascade’s preventative approach, which did not restrict enrolment to parents with poor HRQL or high distress. Aligning with parents in other studies [ 23 , 72 , 73 , 74 ], many of our participating parents actually reported good HRQL and low depression/anxiety at baseline (Q1) and may have had a low need for further help, limiting the relative improvement that could be achieved. It is possible that a program delivered further off treatment, when survivors’ risk of late medical complications and challenges of developing independence into adulthood are increased, may be more effective.…”
Section: Discussionsupporting
confidence: 69%
“…Some also expressed surprise that the program was developed for their personal therapeutic benefit, rather than being purely to support research. It may therefore be helpful in future programs to assess participants’ expectations and preferred types of treatment before they commence a group [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…however, there is a subset of parents who experience high levels of distress after their child completes cancer treatment [24,25]. These ndings highlight the need for caregiver support and education during their child's transition to survivorship care; augmented survivorship education may be one approach to mitigate caregiver distress.…”
Section: Discussionmentioning
confidence: 99%
“…Auch lange nach Erstdiagnose erfahren SCC körperliche Beschwerden wie chronische Fatigue oder Schmerzen [13,16], Progredienzängste [8] sowie Probleme in Sozialbeziehungen zu Peers und Eltern [24]. Auch intrafamiliäre Konflikte zwischen Eltern können SCC belasten [17]. Sie haben in der Folge ein erhöhtes Risiko für Angst und depressive Symptome, verringerten Bildungs-und Berufserfolg sowie Defizite in der Sozialkompetenz [4].…”
Section: Hintergrundunclassified